Shoreline Variability at a Reef-Fringed Pocket Beach - Risandi, Johan; Hansen, Jeff E.; Lowe, Ryan J.; Rijnsdorp, Dirk P. (Frontiers in Marine Science, 2020)
Pocket beaches bound by headlands or other geologic features are common worldwide and experience constrained alongshore transport that influence their morphological changes. Pocket beaches fringed by shallow reefs have not been well-studied, yet can be commonly found throughout temperate and tropical regions. The presence of these reefs are expected to drive distinct hydrodynamics and shoreline responses to offshore waves and water levels, which is investigated in this study. To examine the parameters governing the shoreline variability, a 20-month field study was conducted on a reef-fringed pocket beach in southwestern Australia (Gnarabup Beach), using a series of in situ wave and water level observations, topographic surveys, as well as video shoreline monitoring. The results indicate the beach as a whole (alongshore averaged) was in a stable state. However, we observed substantial spatial variability of the local shorelines in response to offshore wave and water levels across a range of time-scales (from individual storms to the seasonal cycle). We observed local regions of beach rotations within cells partitioned by headlands and offshore reefs. The shoreline response was also dictated by the combination of offshore waves and water level which varied seasonally, with the shoreline generally retreating with lower water levels for the same wave height. Despite the contrasting responses in different alongshore locations of the beach, the overall beach volume of the pocket beach was largely conserved.